Analysis of the Role of Teamwork in Improving Sales Performance at PT. Alfa Scorpii Sentral Yamaha Medan - Nelfita, Natasyah; Syahreza, Dina Sarah; Aprinawati, Aprinawati; Rumapea, Yesayas Roganda; Natasya, Eva; Syahputra, Muhammad Reza (Economic: Journal Economic and Business, 2024)
This study aims to analyze the role of teamwork in improving sales performance at PT. Alfa Scorpii Sentral Yamaha Medan. Facing increasingly fierce competition in the automotive industry, the company encounters challenges related to the effectiveness of teamwork, including communication issues, unequal member involvement, and unclear task distribution. Using a qualitative approach through a case study method, this research identifies that good leadership, mutual trust among team members, and organizational support are key factors that strengthen teamwork. The findings indicate that teamwork plays a significant role in enhancing operational efficiency, strengthening customer relationships, and facilitating collective achievement of sales targets. This study recommends team skill training, improving communication transparency, implementing team-based incentives, and strengthening the role of supervisors to foster a work environment that supports effective teamwork.